Future-robust product portfolio development: insights into the advancement of product portfolios in companies – an interview study - Schlegel, Michael; Just, Markus; Wiederkehr, Ingrid; Thümmel, Carsten; Kempf, Christoph; Koldewey, Christian; Dumitrescu, Roman; Albers, Albert (Proceedings of the Design Society)
Abstract A volatile environment and an increasing number of products along with a growing range of functions pose a challenge for companies when it comes to further development. Existing methods are no longer sufficient to cope with these challenges. In order to develop new methods, the process and challenges in the advancement of product portfolios must be understood. In this paper we conduct an interview study with ten experts to gain a better understanding of the advancement of product portfolios. Triggers, changes and actions are examined and goals and requirements for new methods are derived.

Towards the digital factory twin – design guide for creating a 3D factory model - Disselkamp, Jan-Philipp; Grothe, Robin; Lick, Jonas; Schütte, Ben; Brüne, Sascha; Schröder, Luca; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract Shorter product lifecycles are also leading to even shorter planning times for the development of production systems. In most companies, the restructuring is carried out within a few weeks during the annual holidays. Digital tools such as simulations or the digital twin are used to avoid delaying the restructuring during this time. However, the introduction of a 3D model of the factory is often the first point of failure for many companies. This article proposes a six-step process model that enables the transition from 2D to 3D design. The process model was evaluated in a research project.

Drivers and barriers for design and designers in interdisciplinary product development – a literature-based conceptual model - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract Design is associated with many benefits for businesses, ranging from successful products and brands to greater economic success. However, companies still have difficulties in unlocking the potential of design. This publication develops a literature-based conceptual model that outlines necessary organizational factors and their interrelation to create an environment for design and designers to thrive. At the same time, it explains why companies are having difficulties in leveraging the benefits of design. Further research directions are derived to strengthen the role of design and designers.

Digital twins to increase sustainability throughout the system life cycle: a systematic literature review - Trienens, Malte; Rasor, Rik; Kharatyan, Aschot; Dumitrescu, Roman; Anacker, Harald (Proceedings of the Design Society)
Abstract Sustainability is not a new trend, but a mandatory measure for responsible and environmentally conscious use of resources. The digital transformation offers new potential in engineering and competitive advantages for companies through innovative technologies like the digital twin. Based on digital twins, products can be optimized, and new business models can be developed. Long-term added value is generated for manufacturing companies and customers. This paper explores the benefits of digital twins in the context of sustainability. Current challenges and use cases of digital twins are analysed.

Utilization of the system architecture in the context of validation in the business-to-business (B2B) sector - Humpert, Lynn; Wilke, Daria; Brueggemann, Sarah; Anacker, Harald; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The European Green Deal aims to reduce global emissions by minimizing the use of resources. Early validation of products helps to reduce rework, costs and therefore resources. However, validation of complex mechatronic products is challenging due to interdependencies. Companies are applying systems engineering to meet this challenge. Current validation approaches are insufficient in the early design phases. This paper presents an approach to validation using the system architecture in the B2B sector. A machine tool and a custom built machine are presented as evaluation examples.

Principles for the design of system of systems exemplified using modularisation - Günther, Matthias; Seidenberg, Tobias; Anacker, Harald; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In the context of system of systems (SoS) engineering, the incorporation of design principles is critical to guide the engineering process. This paper presents a systematic literature review to synthesize a list of principles tailored for SoS. 26 principles were identified as generic principles and 39 were mapped to the specific challenges in SoS engineering. Through an evaluation using the principle of modularisation in the design of a charging infrastructure, the study offers insights into the real-world effectiveness of these principles, showing their relevance in SoS engineering tasks.

Challenges of the integrative product and production system development - Disselkamp, Jan-Philipp; Schütte, Ben; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract Shorter product lifecycles and a shift from mechatronic to cyber-physical systems are leading to greater product complexity. This complexity can be addressed by more intensive cooperation between product and production system development. Despite intensive development in recent years, these process models have not been able to establish themselves in corporate practice. Therefore, this paper analyses the existing integrative product and production methods to identify the reasons for their lack of use in practice. The analysis has shown that there are nine barriers.

Interdisciplinary system lifecycle management – a systematic literature review - Wyrwich, Fabian; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The increasing proportion of software in technical products means that both the products and the associated development processes are becoming more complex. An integration of the existing lifecycle considerations Application Lifecycle Management and Product Lifecycle Management into an interdisciplinary System Lifecycle Management promises to make the complexity manageable. To obtain an overview of the current benefits, challenges, requirements, approaches and open research gaps in the context of an ALM-PLM integration, this contribution presents the results of a Systematic Literature Review.

GenAI-Tools revolutionieren die Produktentwicklung - Dumitrescu, Roman; Falkowski, Tommy; Hovemann, Aschot; Rasor, Rik (KEM Konstruktion Automation)

Bildungsforschung – Erziehungswissenschaftliche Perspektiven

The association between dairy intake in adolescents on inflammation and risk markers of type 2 diabetes during young adulthood: results of the DONALD study - Hohoff, Eva; Jankovic, Nicole; Perrar, Ines; Schnermann, Maike; Herder, Christian; Nöthlings, Ute; Libuda, Lars; Alexy, Ute (Public Health Nutrition)
Abstract Objective: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, non-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. Design: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on high-sensitivity C-reactive protein, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as Homeostasis Model Assessment Insulin Resistance in an open-cohort study. Setting: Dortmund, Germany. Participants: Data from participants ( n 375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-d weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. Results: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all P > 0·05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all P > 0·05). Conclusions: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette E. (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Transitivity in finite general linear groups - Ernst, Alena; Schmidt, Kai-Uwe (Mathematische Zeitschrift)
It is known that the notion of a transitive subgroup of a permutation group $G$ extends naturally to subsets of $G$. We consider subsets of the general linear group $\operatorname{GL}(n,q)$ acting transitively on flag-like structures, which are common generalisations of $t$-dimensional subspaces of $\mathbb{F}_q^n$ and bases of $t$-dimensional subspaces of $\mathbb{F}_q^n$. We give structural characterisations of transitive subsets of $\operatorname{GL}(n,q)$ using the character theory of $\operatorname{GL}(n,q)$ and interpret such subsets as designs in the conjugacy class association scheme of $\operatorname{GL}(n,q)$. In particular we generalise a theorem of Perin on subgroups of $\operatorname{GL}(n,q)$ acting transitively on $t$-dimensional subspaces. We survey transitive subgroups of $\operatorname{GL}(n,q)$, showing that there is no subgroup of $\operatorname{GL}(n,q)$ with $1<t<n$ acting transitively on $t$-dimensional subspaces unless it contains $\operatorname{SL}(n,q)$ or is one of two exceptional groups. On the other hand, for all fixed $t$, we show that there exist nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on linearly independent $t$-tuples of $\mathbb{F}_q^n$, which also shows the existence of nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on more general flag-like structures. We establish connections with orthogonal polynomials, namely the Al-Salam-Carlitz polynomials, and generalise a result by Rudvalis and Shinoda on the distribution of the number of fixed points of the elements in $\operatorname{GL}(n,q)$. Many of our results can be interpreted as $q$-analogs of corresponding results for the symmetric group.

Auswertung der modalen Dämpfung von geführten akustischen Wellen in faserverstärkten Kunststoffplatten - Claes, Leander; Hetkämper, Tim; Zeipert, Henning; Henning, Bernd (22. GMA/ITG-Fachtagung – Sensoren und Messsysteme 2024)

Influence of process variations on clinch joint characteristics considering the effect of the nominal tool design - Zirngibl, C; Goetz, S; Wartzack, S (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Focusing on upcoming challenges in lightweight design, such as increasing emission targets or novel multimaterial connections, versatile applicable and environmentally friendly production technologies are crucial. In this context, mechanical joining technology clinching offers a fast and energy-efficient procedure for assembling sheet metals, being a proper alternative to established joining methods, such as spot welding. However, the design of clinch points is a challenge, which is partly supported by numerical or data-based approaches for optimal tool dimensions assuring proper joint characteristics. While this is usually done for an ideal environment, real joining processes are characterized by multiple inevitably varying parameters, e.g. of the material, which have a significant impact on the quality of clinch points. Therefore, this contribution addresses the current gap by analyzing the effect of parameter variations or uncertainties on the resulting joint characteristics and studying the impact of the nominal tool design. Thus, an efficient meta-model-based variation simulation procedure is proposed and used for analyzing the effect of different tool design configurations and variation scenarios. Based on the results, it was found that varying process parameters have a strong impact on the resulting joint characteristics, whereby the effect significantly depends on the nominal tool design. This reveals the potential for a robust tool design and implies that the nominal tool design and the tolerancing of parameters should be done simultaneously for a reliable virtual joining point design without extensive iterations and physical tests.

Identifying K-12 Students' Approaches to Using Worked Examples for Epistemic Programming - Hüsing, Sven; Sparmann, Sören; Schulte, Carsten; Bolte, Mario (Proceedings of the 2024 Symposium on Eye Tracking Research and Applications)

Students’ academic motivation in relation to peer interactions and social environment considering behavioral problems using the experience sampling method - Knickenberg, Margarita; Zurbriggen, Carmen

Effekte von Peerinteraktionen und des sozialen Umfelds auf die aktuelle Motivation von Schüler*innen - Knickenberg, Margarita; Zurbriggen, Carmen

Certifying the Topology of Quantum Networks: Theory and Experiment - Weinbrenner, Lisa T.; Prasannan, Nidhin; Hansenne, Kiara; Denker, Sophia; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine; Gühne, Otfried (Physical Review Letters)

Adaptives Lernen im inklusiven Unterricht aus der Perspektive von Grund- und Förderschullehrkräften – Ergebnisse aus einer Interviewstudie. Posterpräsentation auf der Herbsttagung 2024 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF). - Löper, Marwin Felix; Knickenberg, Margarita; Kretzer, Theresa; Schulze, Jan Roland; Hellmich, Frank